Estudo morfológico e composicional de zircão dos granitos São Jorge Antigo e São Jorge Jovem, Província Aurífera do Tapajós, com base em Microscopia Eletrônica de Varredura e análises de EDS: implicações petrológicas e metalogenéticas - CARVALHO, Thiago Andrade de (2019)
Zircons from Sn-mineralized granites (± W, Ta, Nb) show high contents of Hf and low Zr/Hf ratios, which can be interpreted as an inherited signature of evolved granitic melts or as a result of hydrothermal alteration of host rocks by fluorine rich fluids. Moreover, not specialized granite zircons show lower contents of Hf and comparatively high Zr/Hf ratios. Specialized granites of the tin-Provinces of southern Pará, Pitinga (AM), Rondônia, Goiás and SE Finland have zircons enriched in Hf, Y, Th, U and Ca and lower Zr/Hf ratios when compared to zircons from not mineralized Redenção and Bannach granites, belonging to the Jamon Suite, southeastern Amazonian Craton, and Santa Rosa porphyry granite, São Félix do Xingu region, indicating that the zircon composition can be a useful guide for the preliminary assessment of the metallogenic potential of tin-granites. In this paper, semiquantitative analysis of trace elements were performed by EDS (Energy Dispersive Spectroscopy) in zircons from Old São Jorge Granite (OSJG) and Young São Jorge (YSJG) occurring in the Tapajós Gold Province (TGP), State of Pará, with Pb-Pb crystallization ages in zircon of 1981 ± 2 Ma and 1891 ± 3 Ma, respectively. The YSJG cut OSJG and carries the São Jorge hydrothermal gold deposit. The aim of this study is to verify if the YSJG zircons keep, as well as tin-granites zircons, a characteristic geochemical signature of hydrothermal processes responsible for mineralization, comparing it to the OSJG zircons, which is not mineralized. Zircon crystals were analyzed from OSJG outcrop and borehole samples of the YSJG, from less to the most intensely hydrothermalized rocks and with the largest gold content. Binary diagrams involving Zr, Bi, Te and U, the Zr/Bi and Zr/Te ratios and the Hf+U+As+Bi+Te sum allowed a better grouping of the mineralized body zircons and a clearer separation between these and that from barren OSJG. The zircons of the mineralized zone had the lowest Zr/Bi (≤50) and Zr/Te ratios when compared with the zircons of OSJG, although there is a small overlap. The SEM-EDS methodology for the zircon compositional characterization can be, like the studies of tin-rock zircons, an important complementary tool in the study of hydrothermal gold deposits.